1996
DOI: 10.1088/0029-5515/36/12/i07
|View full text |Cite
|
Sign up to set email alerts
|

Alternating current operation with multicycles in the CT-6B tokamak

Abstract: Stable and clean AC tokamak discharges with two, four and eight cycles of alternating plasma current have been achieved in the CT-6B tokamak. Although there are differences in the plasma-wall interactions in the two halves of each AC cycle, the purity of the plasma is not significantly affected. The finite electron densities during the current reversal phases of each cycle are attributed to a non-zero particle confinement time even at zero current. The plasma parameters in the boundary region during the AC ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 9 publications
0
22
1
Order By: Relevance
“…ISTTOK achieved a multi-cycle alternating square wave plasma with seven half-cycles, no dwell time and a plasma current of 4-5 kA [8]. Constant ac discharges with 2, 4 and 8 sinusoidal cycles of 4 kA were obtained on the CT-6B tokamak [9,10]. Due to the toroidal field duration limit, most ac operations were very short and plasma parameters were relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…ISTTOK achieved a multi-cycle alternating square wave plasma with seven half-cycles, no dwell time and a plasma current of 4-5 kA [8]. Constant ac discharges with 2, 4 and 8 sinusoidal cycles of 4 kA were obtained on the CT-6B tokamak [9,10]. Due to the toroidal field duration limit, most ac operations were very short and plasma parameters were relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…STOR-1M is a small tokamak (R=22 cm, a=3.5 cm), but these results were verified on a larger device STOR-M [8]. Mitarai et al on STOR-M [9,10] and Yang et al on CT 6B [11] concluded that there is indeed a finite plasma density during the current reversal resulting in a smaller breakdown voltage being required for the second pulse.…”
Section: Introductionmentioning
confidence: 95%
“…The study of plasma equilibrium and techniques to maintain plasma equilibrium without rotational transform is important for AC tokamak operation in particular, and also more generally, for the equilibrium issues related to the current-free region of conventional tokamaks. In the CT-6B tokamak, direct insertion of magnetic probes into the AC discharge revealed localized positive and negative currents simultaneously existing in different regions during the current reversal regime [11]. However, within experimental uncertainties, the scenario of opposing currents has been ruled out in the current-free region in JET.…”
Section: Introductionmentioning
confidence: 99%
“…These phenomena are generally observed in several tokamaks such as Stor-1M [17,18], CT-6B [19,20], and HT-7 [21] and so on when alternating current (AC) operation is applied. In these experiments, the plasma configurations are closely related to the current-hole region observed in large tokamak experiments, and several families of nested magnetic surfaces separated by intersecting critical surfaces are clearly shown [22].…”
Section: Introductionmentioning
confidence: 99%